Daya Prediksi Nilai Rapor Terhadap Hasil Uji Kompetensi Keahlian Siswa SMK Negeri pada Kompetensi Keahlian Bisnis Konstruksi dan Properti - Fadhila, Nurul Sonda (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
This study aims to determine the predictive power of the report card value to the results of the competency test of the expertise students' expertise in Construction and Property Business for the 2020/21 school year. During the learning process and the implementation of competency tests of expertise conducted under the Covid-19 pandemic, the value of the report card assigned to group C3 (expertise package) is utilised. Due to the use of representative samples from the entire population, this research population consists of sixty-five students. Documentation-based data collection methods. Simple linear regression analysis is used to predict the direction of a positive or negative relationship between the skill competency test variable and the report card value variable and to predict whether or not the skill competency test variable is influential if the report card value variable changes. Normality, linearity, and heteroskedasticity tests are performed before data analysis as prerequisites. The study's results demonstrated that the predictive power of the report card score to the results of the competency test of expertise is positive, such that as the value of the report card increases, so do the results of the competency test of expertise. There is a relationship between the variable value of the report card and the results of the competency test of expertise.